A comprehensive physicochemical, thermal, and spectroscopic characterization of zinc (II) chloride using X‑ray diffraction, particle size distribution, differential scanning calorimetry, thermogravimetric analysis/differential thermogravimetric analysis, ultraviolet‑visible, and Fourier transform‑infrared spectroscopy - Trivedi, Mahendra Kumar; Sethi, Kalyan Kumar; Panda, Parthasarathi; Jana, Snehasis (International Journal of Pharmaceutical Investigation)
Objective: Zinc chloride is an important inorganic compound used as a source of zinc and has other numerous industrial applications. Unfortunately, it lacks reliable and accurate physicochemical, thermal, and spectral characterization information altogether. Hence, the authors tried to explore in‑depth characterization of zinc chloride using the modern analytical technique. Materials and Methods: The analysis of zinc chloride was performed using powder X‑ray diffraction (PXRD), particle size distribution, differential scanning calorimetry (DSC), thermogravimetric analysis/differential thermogravimetric analysis (TGA/DTG), ultraviolet‑visible spectroscopy (UV‑vis), and Fourier transform‑infrared (FT‑IR) analytical techniques. Results: The PXRD patterns showed well‑defined, narrow, sharp, and the significant peaks. The crystallite size was found in the range of 14.70–55.40 nm and showed average crystallite size of 41.34 nm. The average particle size was found to be of 1.123 (d10), 3.025 (d50), and 6.712 (d90) μm and average surface area of 2.71 m2/g. The span and relative span values were 5.849 μm and 1.93, respectively. The DSC thermogram showed a small endothermic inflation at 308.10°C with the latent heat (ΔH) of fusion 28.52 J/g. An exothermic reaction was observed at 449.32°C with the ΔH of decomposition 66.10 J/g. The TGA revealed two steps of the thermal degradation and lost 8.207 and 89.72% of weight in the first and second step of degradation, respectively. Similarly, the DTG analysis disclosed Tmax at 508.21°C. The UV‑vis spectrum showed absorbance maxima at 197.60 nm (λmax), and FT‑IR spectrum showed a peak at 511/cm might be due to the Zn–Cl stretching. Conclusions: These in‑depth, comprehensive data would be very much useful in all stages of nutraceuticals/pharmaceuticals formulation research and development and other industrial applications.
Keywords: Differential scanning calorimetry; particle size distribution; powder X‑ray diffraction; thermogravimetric analysis; zinc chloride